The Silent Struggle: Understanding the Burden of Mental Illness on Families, Caregivers and Its Impact - (:unkn) unknown (My University, 2025)
This review explores the vicarious burden on family caregivers of individuals with mental illnesses, particularly in Africa, where cultural stigma, economic disparities, and clinical gaps amplify caregiver strain. Families worldwide bear emotional, financial, and social burdens, but African caregivers encounter significant stress due to cultural norms that link mental illness to supernatural causes, gendered caregiving roles, and underfunded health systems. Economic constraints force families into catastrophic healthcare costs, while fragmented services leave caregivers managing crises without support. Consequences of the lived experience include psychological distress and depression rates that are higher than those of non-caregivers. Culturally tailored interventions, such as psychoeducation in Nigeria and Zimbabwe’s community-led Friendship Bench project, reduce distress by 50%. Respite care and policies provide partial relief. The review advocates for holistic reforms: dismantling stigma, integrating caregivers into care systems, and investing in mental health infrastructure. Prioritizing community engagement, task-shifting programs, and equitable resource allocation can alleviate suffering and foster resilience. Addressing cultural, economic, and clinical intersections is vital to advancing mental health outcomes for caregivers and patients in Africa and beyond.
Keywords: African Research